Konstitusi Myanmar Tahun 2008: Pembagian Kekuasaan Antara Sipil-Militer pada Masa Pemerintahan Sipil Usdp (2011-2016) & Nld (2016-2021) di Myanmar - Miftah Awaludin Najib; Chusnul Mar'iyah (Jurnal Syntax Admiration, 2024)
This study aims to analyze civil-military relations during the USDP and NLD governments, as well as analyze the democratic transition in Myanmar that led to the division of power during the civilian rule. This research was conducted using qualitative research methods. That is, a method that is used by providing an overview of the problem being discussed by arranging the facts in such a way that it forms a configuration of the problem that can be understood clearly. This approach has an assumption by seeing social reality as an ever-changing condition and is the result of social construction between actors and social institutions. As a result, under the 2008 Constitution, the military in Myanmar remains dominant in security and defense with 25% of legislative seats reserved for the Tatmadaw. This division of power is unequal, resulting in military dominance, as the democratic transition is controlled by the military through a "seven-step roadmap to democracy," without the significant role of the NLD. Civilian control over the military during the 2011-2021 civilian rule was not achieved, with the military having sovereign authority in top-down policies and weak political representation.